Determination of Thiocyanate by Kinetic Spectrophotometric Flow Injection Analysis - Mohsen Keyvanfard; Khadijeh Alizad; Parinaz Elahian (Journal of Chemistry)
A simple and rapid flow injection spectrophotometric method has been developed for the determination of amount of thiocyanate in wastewaters and well water samples. It is based on the reaction of thiocyanate in hydrochloric acid with janus green and bromate. Reaction was monitored spectrophotometrically by measuring janus green absorbance at λmax=554 nm. The calibration graph was linear over the range 0.02–1.0 μg mL−1 and the detection limit was 0.016 μg mL−1 (s/n=3). The throughput was 25 samples per hour.